Ensino de leitura e escrita para crianças surdas - Tenório, Jacqueline Pimentel (2018)
Hearing losses may lead to delays in the development of auditory function, language acquisition, and learning of academic skills, such as reading and writing. The effectiveness of the instructional curriculum "Learning to Read and Write in Small Steps-ALEPP (in Portuguese)" has been empirically demonstrated with several populations, but the results for the deafs are still scarce. The present study aimed to describe and evaluate the effects of ALEPP on the reading and writing repertoire of children with hearing impairment. In Study 1 the participant's phonological performance was assessed using the ABFW language test, before, during and after exposure to ALEPP, applied by the researcher. In Study 2 the ALEPP was applied by a group of teachers of the Specialized Educational Assistance and supervised by the experimenter. In both studies participants were exposed to two computerized modules (1 and 2) of ALEPP. The purpose of Module 1 was to teach 60 simple words from Brazilian Portuguese and to test 33 other words with similar structure, composed by the recombination of the syllables of previously taught words. Module 2 aimed to teach Portuguese words with variations in grapheme-phoneme correspondences, such as consonant clusters and digraphs. In Study 1 the participant was a 6-year-old boy, with moderate to profound bilateral sensorineural hearing loss. This child was a user of Individual Sound Amplification Apparatus, who had been oralized and presented zero scores in reading and dictation tasks evaluated through the Reading and Writing Network Assessment. After exposure to the two teaching modules, the boy showed an increase in reading scores for both groups of words (teaching and generalization). The results also indicated the occurrence of changes in the participant’s phonological processes after exposure to the teaching procedure. In Study 2 participants were eight hearing impaired children, aged nine to 12 years, users of sound amplification devices and Frequency Modulation System, who showed low reading scores in the Reading and Writing Network Assessment or in the Initial Evaluation of the Module 2. Two of the eight participants, EMM and KCSC, were exposed to the two teaching modules and all participants (including those exposed only to Module 1 or 2) acquired reading and writing repertoires involving taught words and words formed by recombination of syllables. The results extended to hearing impaired students, the findings on the effectiveness of ALEPP to teach reading and writing repertoires, thus confirming the feasibility of its application by teachers. It is concluded that ALEPP is an efficient tool that can be useful in the rehabilitation process of deaf individuals.